Evaluation of the Application Effect of "Yilian Family Medical Health Service Platform" in the Health Education for Cardiovascular Patients - Xiaohe XU; Li QU (Tehran University of Medical Sciences, 2020)
Background: To explore the effect of the "Yilian Family Medical Health Service Platform" used by cardiology nurses on the health education of cardiovascular patients. Methods: Overall 380 patients with coronary heart disease were selected from the Second Hospital of Dalian Medical University, Dalian China in 2019. They were divided into control group (190 cases) and observation group (190 cases) according to the method of digital random allocation. The traditional discharge health education model was used in control group, that is, oral education before discharge. On the basis of traditional health education, the "Yilian Family Medical Health Service Platform" was recommended in the observation group. Patients could use the platform to communicate and consult with the family doctor team. The awareness of disease and medication, compliance, incidence of rehospitalization, and satisfaction with nursing work were compared in the two groups after discharge from the hospital. Results: The experimental group was significantly better than the control group in terms of disease awareness, medication adherence, return visits, and rehospitalization (P <0.05). Conclusion: The "Medical Federation Family Medical Health Service Platform" could be used by nurses as a continuation of health education for patients with cardiovascular disease after discharge from the hospital. It can promote patient recovery, improve medication compliance, reduce the rate of rehospitalization, and obviously improve patients' satisfaction to the nursing staff.